Blood microsampling using capillaries for drug-exposure determination in early preclinical studies: a beneficial strategy to reduce blood sample volumes. (February 2014) - Dillen, Lieve; Loomans, Tine; Van de Perre, Guy; Versweyveld, Dries; Wuyts, Koen; de Zwart, Loeckie
Background: Capillary microsampling (CMS) of blood with subsequent blood analysis offers a potential strategy to deal with increased demand to reduce blood sample volumes in animal discovery and preclinical studies.Results: A generic approach is presented allowing PK analysis in 15 µl blood samples. CMS blood exposure data were compared with the traditional plasma exposure results in rats and dogs. Blood PK profiles obtained for two different compounds were in agreement with profiles obtained in plasma. From these studies ex vivo blood to plasma ratios were also obtained. In a mouse study, blood PK profiles that were obtained following automatic sampling overlay with the blood PK profiles obtained with CMS.Conclusion: CMS in 15 µl glass capillaries allows collection and handling of small and exact volumes of blood. Although CMS can also be applied for plasma collection, the full benefit is only achieved with blood collection and analysis.